Diagnostics of the Organizational Factors Contributing to Work at Retirement Age - Kirnos Inna O. (Problemi Ekonomiki, 2018)
The aim of the publication is to substantiate the research method and to clarify the content of the diagnostic tool for identifying the career goals, specific needs of older workers, and their perception of the organizational climate regarding the continuation of work at retirement age. An authentic questionnaire for 50+ employees is proposed as a universal tool for diagnosing the organizational climate for working at retirement age. In developing the questionnaire, the sectional approach was used, according to which the questions are grouped into content blocks: career preferences, desired working conditions, perception of opportunities for development, perception of organizational support, age accounting in personnel policy, emotional attachment to the organization, perception of age discrimination. The proposed questionnaire is a universal diagnostic tool that can be applied at enterprises of any field of activity. It provides feedback between staff and management, and the results of the survey form a factual basis for developing an organizational climate strategy for successful aging in the workplace and retention of older workers.